Caracterização pedológica de saprolitos de gnaisse e de basalto, e implicações para o desenvolvimento de plantas - Wangen, Dalcimar Regina Batista (2012)
Saprolite may be very thick in regions with humid tropical and subtropical climates. Depending on the degree of fracturing, saprolite can restrict root development and water movement throughout the profile. However, saprolite that has undergone greater alteration can function like soil in terms of drainage, water storage, nutrient supply and physical support for plants. Our objective was to contribute to knowledge about saprolite and its importance for plant development. Samples were collected from four soil-saprolite profiles located under second-growth forests. Soils from three of these profiles were classified as Haplustoll (two derived from basalt and one from gneiss - profiles 1, 2 and 3, respectively) and soil from the remaining profile was classified as Ustochrept derived from gneiss (profile 4). The samples were characterized by standard physical and chemical analyses, mineralogical analysis by X-ray diffraction (XRD), and geochemical analysis via identification of the most significant elements (expressed as oxides) of the constituent minerals. The basalt profiles were finely textured and had higher total pore volumes (~55% and 65% in profiles 1 and 2, respectively), whereas the gneiss profiles had coarser texture and lower total porosity (~ 45 % and 40 % in profiles 3 and 4, respectively). The microporosity of the saprolite was 39-46 %, 48-56 %, 23-43 % and 30-37 %, in profiles 1, 2, 3 and 4, respectively. The clay of the basalt profiles contained mica, smectite, kaolinite, anatase, hematite and gibbsite whereas the coarse sand contained feldspar, muscovite, vermiculite, halloysite-metahalloysite (kaolinite?), quartz, ilmenite, anatase, magnetite, maghemite and goethite. The mineral compositions of the gneiss profiles differed substantially from each other. Profile 3 had the greatest number of minerals with talc, calcite, illite, smectite, kaolinite, anatase, rutile, goethite and gibbsite in the clay and chlorite, interstratified chlorite-vermiculite, feldspar, amphibole, pyroxene, staurolite, pyrophyllite, quartz, ilmenite, rutile, anatase, magnetite, titanite and goethite in coarse sand. In profile 4, muscovite, kaolinite, rutile and gibbsite were identified in the clay and chlorite, feldspar, mica, magnetite, muscovite, quartz and rutile were identified in the sand. In the basalt saprolite, pH in water ranges from high (6.1 to 7.0) to very high (> 7.0), Al3+ saturation is zero, base saturation is very good and cation exchange capacity (CEC) is very good in profile 1 (> 15 cmolc dm-3) and good in profile 2 (8.61 to 15 cmolc dm-3). In the gneiss saprolite (profile 3) the pH in water varies from high (6.1-7.0) to very high (>7), Al3+ saturation is zero and base saturation and CEC are both very good. These numbers contrast with those of the gneiss saprolite (profile 4) where pH is low (4.5 to 5.4), Al3+ saturation is average (30.1-50.0%), base saturation is low (≤ 20 %) and CEC is very low (≤ 1.6 cmolc dm-3). These values indicate greater weathering and leaching. We concluded that basalt and gneiss saprolites have great potential to store and supply water to plants. However, the ability of these saprolites to supply nutrients varies with the degree of weathering and leaching. Saprolite under Haplustoll soil has considerable potential to supply nutrients to plants, unlike the much poorer saprolite under Ustochrept soil. There is a direct relationship between the soil and its underlying saprolite. This is especially significant for woody plants in this region of the regolith given that their root development occurs in the soil and the saprolite.